2018
DOI: 10.1177/0033354918795442
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and Take-home Lead Exposure Among Lead Oxide Manufacturing Employees, North Carolina, 2016

Abstract: Integration of child and adult BLL surveillance activities identified an occupational source of lead exposure among workers and associated children. Our findings support recent recommendations that implementation of updated lead standards will support better control of lead in the workplace and prevent lead from being carried home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Similar to our results, previous studies on lead monitoring in occupationally exposed workers reported BLLs between four to seven times higher than in controls (not occupationally exposed) and higher BLLs in men than women ( Kasuba et al, 2020 ; Shraideh et al, 2018 ). Another study on occupational lead exposure noted that 71% of employes at a lead oxide manufacturing presented BLLs >30 μg/dl ( Rinsky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our results, previous studies on lead monitoring in occupationally exposed workers reported BLLs between four to seven times higher than in controls (not occupationally exposed) and higher BLLs in men than women ( Kasuba et al, 2020 ; Shraideh et al, 2018 ). Another study on occupational lead exposure noted that 71% of employes at a lead oxide manufacturing presented BLLs >30 μg/dl ( Rinsky et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…contribute to “ take home Pb ” where children are secondarily exposed to Pb at home from their occupationally-exposed parents or adults siblings through inhalation or contact of Pb particles on clothes. 35 , 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…The high proportion of respondents who did not have measures to prevent lead dust from leaving the workplace is consistent with previous reports of workers wearing personal clothing into and out of workplaces; employers not providing or enforcing the use of personal protective equipment, uniforms, and showers; and even a complete lack of training on lead hazards in the workplace. 1,9,11,29,30 Previous studies that sampled lead dust on the floors of employee vehicles found a median of 1570 µg/ft 2 for workers in lead paint remediation and metal recycling industries, 9 a mean of 40.3 µg/ft 2 for workers in the lead paint remediation industry, 2 and geometric means of 818 µg/ft 2 and 177 µg/ft 2 for bridgeworkers. 29,31 The overall geometric mean of 234 µg/ft 2 we observed is in the middle of these previous measurements, although we found that the industry with the highest levels, lead acid battery recycling (geometric mean = 3227 µg/ft 2 ), was notably higher.…”
Section: Discussionmentioning
confidence: 99%